A Study Working of Buddhadasa that Affected the Propagation of Buddhism in Thai Society - Santamano (Wisakha), Phra Noy (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 2 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
This research There are 3 objectives: (1) to study the principles and methods of propagating Buddhism in Thai society. (2) to study the principles and methods of propagating Buddhism in Thai society. (3) to analitical the works of Buddhadasa that analisis the works of Buddhadasa that affected the propagation of Buddhism in Thai society. The research found that. Principles and methods of propagating Buddhism in Thai society The Lord Buddha has announced the policy of propagating Buddhism in three ways: (1) He taught for the listeners to know the truth. (2) teaching to listeners to reflect on. (3) teach to listeners to receive the results of practice. The works of Buddhadasa that affected the propagation of Buddhism in Thai society. That works as politics: Phuttha Phikkhu described the concept of the system "Thamiks Socialism" is a political system that can solve the problem. Economics: Buddhadasa Bhikkhu expressed his views on the topic of finding property for happiness. Means: The work of Buddhadasa that affects the propagation of Buddhism in Thai society. On the promotion of Buddhism: The monks group gave an interview focusing on, The practice of being a model of Buddhadasa. Academic group gave an interview by focusing on, Beliefs in Buddhism. General public group gave an interview by focusing on, Buddhist teachings. In the field of education: The monk group gave an interview focusing on Buddhist texts. Academic group gave an interview by focusing on, Current education is characterized as "taking children to build houses". General public group gave an interview by focusing on, Buddhadasa has created many teaching media. On the social side: The monks group gave an interview focusing on Phutthadasa joined all types of work that were not immoral. Academic group gave an interview by focusing on the works of Buddhadasa Make people have higher minds. General public group gave an interview by focusing on the work of Buddhadasa is a spiritual, physical and verbal mind.